Behavioral Factors and Investment Decisions: Evidence from the Nepal Stock Market - Subedi, Phul Prasad; Sharma, Bhumiswor; Maharjan, Sushan (Journal of Emerging Management Studies, 2025)
Purpose – The aim of this study is to analyze the behavioral biases that affect investment decisions, focusing on five specific biases: availability bias, regret aversion bias, mental accounting, loss aversion bias, and herding behavior.Design/methodology/approach – A descriptive and causal research design was employed, utilizing a structured questionnaire communicated to 386 investors chosen through convenience sampling. The data collection encompassed multiple-choice and Likert-scale questionnaires. Analysis was performed in SPSS (V25) utilizing reliability and validity assessments, descriptive statistics, correlation, and multiple regression methods.Findings and Conclusion – The findings confirm that behavioral biases significantly influence investment choices, often leading to less optimal financial outcomes. Among these biases, herding behavior and loss aversion had the most decisive influence, indicating that investors tend to follow market trends or avoid losses rather than pursue potential gains. Regret aversion bias, however, was statistically insignificant, suggesting that past regret does not substantially affect future investment decisions.Implication – The findings reveal that loss aversion, availability bias, and mental accounting strongly influence Nepalese investors’ decisions. Investors should adopt research-based strategies to minimize these biases. Financial advisors can guide clients toward disciplined investment behavior, while policymakers and regulators can use these insights to enhance financial literacy and develop behaviorally informed market policies that promote rational and informed investment decisionsOriginality/Value – The study emphasizes the need for substantial financial literacy initiatives, focused investor awareness programs, and the implementation of decision-support systems to promote informed and rational investment decisions among market participants.